Summary of animal models of myelodysplastic syndrome - Li, Weisha (Animal Model Exp Med, 2021)
Myelodysplastic syndrome (MDS) is a malignant tumor of the hematological system characterized by long‐term, progressive refractory hemocytopenia. In addition, the risk of leukemia is high, and once it develops, the course of acute leukemia is short with poor curative effect. Animal models are powerful tools for studying human diseases and are highly effective preclinical platforms. Animal models of MDS can accurately show genetic aberrations and hematopoietic clone phenotypes with similar cellular features (such as impaired differentiation and increased apoptosis), and symptoms can be used to assess existing treatments. Animal models are also helpful for understanding the pathogenesis of MDS and its relationship with acute leukemia, which helps with the identification of candidate genes related to the MDS phenotype. This review summarizes the current status of animal models used to research myelodysplastic syndrome (MDS).